Signaling networks controlling ID and E protein activity in T cell differentiation and function - Hwang, Sung-Min; Im, Sin-Hyeog; Rudra, Dipayan (Frontiers in Immunology, 2022)
E and inhibitor of DNA binding (ID) proteins are involved in various cellular developmental processes and effector activities in T cells. Recent findings indicate that E and ID proteins are not only responsible for regulating thymic T cell development but also modulate the differentiation, function, and fate of peripheral T cells in multiple immune compartments. Based on the well-established E and ID protein axis (E-ID axis), it has been recognized that ID proteins interfere with the dimerization of E proteins, thus restricting their transcriptional activities. Given this close molecular relationship, the amount of expression or stability of these two protein families can dynamically affect the expression of specific target genes involved in T cell development and function. Therefore, it is essential to understand the endogenous proteins or extrinsic signaling pathways that can influence the dynamics of the E-ID axis in a cell-specific and context-dependent manner. Here, we provide an overview of E and ID proteins and the functional outcomes of the E-ID axis in the development and function of several T cell lineages, including thymic and peripheral T cell subsets. Further, we review the mechanisms by which endogenous proteins and signaling pathways alter the E-ID axis in various T cell subsets influencing T cell function and fate at steady-state and in pathological settings. A comprehensive understanding of the functions of E and ID proteins in T cell biology can be instrumental in T cell-specific targeting of the E-ID axis to develop novel therapeutic modalities in the context of autoimmunity and cancer.